Dydaktyka historii – wyzwania, dylematy, szanse - Stinia, Maria (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych Instytut Historyczny, 2021)
In contemporary history didactics in Poland, the dominant paradigms are: 1) the objectivist one, which has a strong influence on the educational model commonly used during lessons (objectives, content, course of the lesson, its structure and teaching components) and 2) the instructional one, connected with didactic measurement and operationalization of goals, i.e., is aimed at acquiring the desired behaviour of students and measurability of effects and results. In current paradigms, it is difficult to provide multiperspectivity and to show the controversies that enforce it. The traditional narrative form dominates. Successive curriculum reforms focus more and more on the content of teaching, and increasing their volume limits the acquisition of historical skills, they remain unchanged despite the increase in knowledge. A problem arises whether the goal in itself is historical knowledge, or the students’ ability to harness it in the future.